Effect of price and in-store promotion on sales: a study of distinct regions in an emerging market - Sanchez, Juan Machado (2016)
Increasing competition caused by globalization, high growth of some emerging markets and stagnation of developed economies motivate Consumer Packaged Goods (CPGs) manufacturers to drive their attention to emerging markets. These companies are expected to adapt their marketing activities to the particularities of these markets in order to succeed. In a country classified as emerging market, regions are not alike and some contrasts can be identified. In addition, divergences of marketing variables effect can also be observed in the different retail formats. The retail formats in emerging markets can be segregated in chain self-service and traditional full-service. Thus, understanding the effectiveness of marketing mix not only in country aggregated level data can be an important contribution. Inasmuch as companies aim to generate profits from emerging markets, price is an important marketing variable in the process of creating competitive advantage. Along with price, promotional variables such as in-store displays and price cut are often viewed as temporary incentives to increase short-term sales. Managers defend the usage of promotions as being the most reliable and fastest manner to increase sales and then short-term profits. However, some authors alert about sales promotions disadvantages; mainly in the long-term. This study investigates the effect of price and in-store promotions on sales volume in different regions within an emerging market. The database used is at SKU level for juice, being segregated in the Brazilian northeast and southeast regions and corresponding to the period from January 2011 to January 2013. The methodological approach is descriptive quantitative involving validation tests, application of multivariate and temporal series analysis method. The Vector-Autoregressive (VAR) model was used to perform the analysis. Results suggest similar price sensitivity in the northeast and southeast region and greater in-store promotion sensitivity in the northeast. Price reductions show negative results in the long-term (persistent sales in six months) and in-store promotion, positive results. In-store promotion shows no significant influence on sales in chain self-service stores while price demonstrates no relevant impact on sales in traditional full-service stores. Hence, this study contributes to the business environment for companies wishing to manage price and sales promotions for consumer brands in regions with different features within an emerging market. As a theoretical contribution, this study fills an academic gap providing a dedicated price and sales promotion study to contrast regions in an emerging market.